Cold-induced [Ca2+]cyt elevations function to support osmoregulation in marine diatoms. Issue 2 (27th July 2022) - Kleiner, Friedrich H; Helliwell, Katherine E; Chrachri, Abdul; Hopes, Amanda; Parry-Wilson, Hannah; Gaikwad, Trupti; Mieszkowska, Nova; Mock, Thomas; Wheeler, Glen L; Brownlee, Colin
Abstract: Diatoms are a group of microalgae that are important primary producers in a range of open ocean, freshwater, and intertidal environments. The latter can experience substantial long- and short-term variability in temperature, from seasonal variations to rapid temperature shifts caused by tidal immersion and emersion. As temperature is a major determinant in the distribution of diatom species, their temperature sensory and response mechanisms likely have important roles in their ecological success. We examined the mechanisms diatoms use to sense rapid changes in temperature, such as those experienced in the intertidal zone. We found that the diatoms Phaeodactylum tricornutum and Thalassiosira pseudonana exhibit a transient cytosolic Ca 2+ ([Ca 2+ ]cyt ) elevation in response to rapid cooling, similar to those observed in plant and animal cells. However, [Ca 2+ ]cyt elevations were not observed in response to rapid warming. The kinetics and magnitude of cold-induced [Ca 2+ ]cyt elevations corresponded with the rate of temperature decrease. We did not find a role for the [Ca 2+ ]cyt elevations in enhancing cold tolerance but showed that cold shock induces a Ca 2+ -dependent K + efflux and reduces mortality of P. tricornutum during a simultaneous hypo-osmotic shock. As intertidal diatom species may routinely encounter simultaneous cold and hypo-osmotic shocks during tidal cycles, we propose that cold-induced Ca 2+ signaling interacts with osmotic signaling pathways to aid in the regulation of cell volume. Our findings provide insight into the nature of temperature perception in diatoms and highlight that cross-talk between signaling pathways may play an important role in their cellular responses to multiple simultaneous stressors. Abstract : A calcium signaling pathway in marine diatoms is activated by cold temperature and enhances survival during simultaneous hypo-osmotic stress.